2017
DOI: 10.1155/2017/5295286
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt5a Signaling in Normal and Cancer Stem Cells

Abstract: Wnt5a is involved in activating several noncanonical Wnt signaling pathways, which can inhibit or activate canonical Wnt/β-catenin signaling pathway in a receptor context-dependent manner. Wnt5a signaling is critical for regulating normal developmental processes, including stem cell self-renewal, proliferation, differentiation, migration, adhesion, and polarity. Moreover, the aberrant activation or inhibition of Wnt5a signaling is emerging as an important event in cancer progression, exerting both oncogenic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…87,88 Wnt5 signaling is critical for regulating normal developmental processes, including stem cell selfrenewal, proliferation, differentiation, migration, adhesion, and polarity. 89,90 Wnt factors are a group of these signaling molecules that act on stem cells within the stem cell niche to help maintain their capacity for self-renewal, and they can activate the β-catenin-dependent pathway. 91,92 Similar to those of previous studies, our findings suggest that F9 cells treated with RA or AgNPs showed upregulation of Wnt5 expression, whereas F9 cells treated with RA or AgNPs in the presence of cisplatin showed reduced expression levels of Wnt5 and Gata6, which confirms that cisplatin inhibits the AgNPs-induced differentiation process via Wnt5 signaling.…”
mentioning
confidence: 99%
“…87,88 Wnt5 signaling is critical for regulating normal developmental processes, including stem cell selfrenewal, proliferation, differentiation, migration, adhesion, and polarity. 89,90 Wnt factors are a group of these signaling molecules that act on stem cells within the stem cell niche to help maintain their capacity for self-renewal, and they can activate the β-catenin-dependent pathway. 91,92 Similar to those of previous studies, our findings suggest that F9 cells treated with RA or AgNPs showed upregulation of Wnt5 expression, whereas F9 cells treated with RA or AgNPs in the presence of cisplatin showed reduced expression levels of Wnt5 and Gata6, which confirms that cisplatin inhibits the AgNPs-induced differentiation process via Wnt5 signaling.…”
mentioning
confidence: 99%
“…An interesting nding in our study is the high rates of positive ROR2-and WNT5A-expression in the normal pancreatic tissues. In adult tissues, expression levels of WNT5A and ROR2 are in general decreased [37] . Thus, the majority of oncological reports tend to speculate the potential of ROR2 and WNT5A as therapeutic targets based on their differential expressions within human malignancies and on the low to absent expression in normal tissues [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the positive expression of WNT5A and ROR2 in the adjacent normal pancreatic tissue as found here, signi es their role in pancreatic tissue physiology and in ammation. The roles of WNT5A-ROR2 axis in normal cells has been demonstrated, involving diverse cellular functions, including cell polarization, migration and stemness [37] . Such prominent cellular processes in the adjacent to PDAC normal pancreatic tissue may dictate the tumor microenvironment in favour of tumor progression and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen known Wnt ligands signal through two classes of receptors—the seven-pass transmembrane Frizzled receptors (FZD; a family with 10 members in mammals) and LRP5/6. Canonical Wnt signaling via LRP5/6 and FZD functions by regulating the amount of β-catenin that is available in the nucleus to control gene expression [ 93 ], whereas non-canonical signaling pathways are those that are independent of β-catenin and utilize FZD (but not LRP5/6) in conjunction with other coreceptors, such as ROR1/2 [ 94 , 95 ]. When Wnt signaling is off, β-catenin is phosphorylated by a complex, including GSK3, CK1, APC, and Axin and targeted for proteosomal degradation.…”
Section: Wnt/β-cateninmentioning
confidence: 99%